Model Literasi Informasi Pengajar Dalam Mengembangkan Model Kecerdasan Ruang Visual (Spatial Intelligence): Studi pada para peserta bimbingan belajar Villa Merah Bandung - Yunus Winoto; Naura Aufa; Rully Khairul Anwar (Pustabiblia: Journal of Library and Information Science, 2020)
This study aims to determine the information literacy patterns of the instructors in developing models of visual space intelligence. This research was conducted at the learning center “Villa Merah” Bandung. The focus of this study includes the views of the teacher’s views on information literacy and the teacher’s literacy pattern in the information seeking process. The method used in this study uses qualitative research with a type of case study research. The technique of collecting data is done through observation, interviews and through library research. Based on the results of the study, it is known that the instructors in tutoring at Villa Merah Bandung are still inaccurate in understanding what is really meant by literacy. Whereas regarding the pattern of literacy if it is associated with the stages of information retrieval based on the big six model such as the stages of problem formulation and identification, strategy formulation, determination of location and access to information, stages of use, selection and synthesis stages and evaluation stages in general the instructors in seeking information has carried out the stages of information retrieval.